Nanohybrids as Protein-Polymer Conjugate Multimodal Therapeutics - Kiran, Pallavi; Khan, Amreen; Neekhra, Suditi; Pallod, Shubham; Srivastava, Rohit (Frontiers in Medical Technology, 2021)
Protein therapeutic formulations are being widely explored as multifunctional nanotherapeutics. Challenges in ensuring susceptibility and efficacy of nanoformulation still prevail owing to various interactions with biological fluids before reaching the target site. Smart polymers with the capability of masking drugs, ease of chemical modification, and multi-stimuli responsiveness can assist controlled delivery. An active moiety like therapeutic protein has started to be known as an important biological formulation with a diverse medicinal prospect. The delivery of proteins and peptides with high target specificity has however been tedious, due to their tendency to aggregate formation in different environmental conditions. Proteins due to high chemical reactivity and poor bioavailability are being researched widely in the field of nanomedicine. Clinically, multiple nano-based formulations have been explored for delivering protein with different carrier systems. A biocompatible and non-toxic polymer-based delivery system serves to tailor the polymer or drug better. Polymers not only aid delivery to the target site but are also responsible for proper stearic orientation of proteins thus protecting them from internal hindrances. Polymers have been shown to conjugate with proteins through covalent linkage rendering stability and enhancing therapeutic efficacy prominently when dealing with the systemic route. Here, we present the recent developments in polymer-protein/drug-linked systems. We aim to address questions by assessing the properties of the conjugate system and optimized delivery approaches. Since thorough characterization is the key aspect for technology to enter into the market, correlating laboratory research with commercially available formulations will also be presented in this review. By examining characteristics including morphology, surface properties, and functionalization, we will expand different hybrid applications from a biomaterial stance applied in in vivo complex biological conditions. Further, we explore understanding related to design criteria and strategies for polymer-protein smart nanomedicines with their potential prophylactic theranostic applications. Overall, we intend to highlight protein-drug delivery through multifunctional smart polymers.